クッサク シリョウ ノ アンテイ ドウイタイ ソセイ カラ ミタ ロストウ ノ カザン カツドウ - 中井, 信之; ナカイ, ノブユキ; 水谷, 義彦; ミズタニ, ヨシヒコ; 和田, 秀樹; ワダ, ヒデキ; NAKAI, Nobuyuki; MIZUTANI, Yoshihiko; WADA, Hideki (国立極地研究所, 1977)
P(論文) 1973年DVDP3による火山岩の掘削が,ロス島のマクマード基地で行われ,その掘削深度は381 mに達した.この掘削でえられた火山岩はアルカリ玄武岩類で,いくつかのlava flowとpyroclastic brecciaであった.これらのコアー中に氷(permafrost ice)と白色塩類(主にthenarditeとcalcite)が存在し,モれらの安定同位体比,すなわちδD, δ^<13>C, δ^<18>O,δ^<34>Sを測定し,過去の火山活動の歴史を推察した.その結果,火山活動は3段階に分けられる.1)深度200～381m : 海底火山による噴出であった.2)深度100～200 m : brackishまたはsubglacialの環境での噴出で,特に酸化環境における強度の熱水作用を受けた特徴がある.3)深度0～100m: 1), 2)とはまったく異なる環境での噴出で,subaerial conditionと考えられた.また地表物質の影響を大きく受けた特徴がある. In 1973, DVDP 3 drill hole near McMurdo Station, Ross Island penetrated lava flows and pyroclastics composed of alkaline basalts and reached 381 m. The basal 214 m thick pyroclastic unit consists of basaltic hyaloclastites. Cores contain permafrost ice as layers, filling the vesicles and cementing pyroclastics. Thenardite and calcite are also present mainly along the icerock interface. The origin of ice and salts was investigated using compositions of stable isotopes to disclose the volcanic events occurred in geologic time. For these purposes, δD, δ^<13>C, δ^<34>S and δ^<18>O were measured using the above-mentioned samples. Theδ^<18>O of ice samples increases substantially with increasing depth, ranging from -35.3‰ near the ground surface to +1.1 ‰ at the bottom of the drill hole. δ^<34>S, δ^<18>O andδ^<13>C values for thenardite and calcite can be divided readily into three groups according to their depth. From the above results, the following conclusions can be obtained. 1) Basaltic hyaloclastites found at a depth of 200 to 381 m were erupted in the submarine volcanism. 2) Lavas and pyoclastics found at a depth of 100 to 200 m were formed under a subglacial and brackish condition, and have undergone strong hydrothermal alteration. 3) Samples from 0 to 100m downhole were erupted in environment quite different from volcanic rocks beneath, suggesting subaerial flow or eruptions. departmental bulletin paper